Removal of Heavy Metals from Steel Making Waste Water by Using Electric Arc Furnace Slag - C. L. Beh; T. G. Chuah; M. N. Nourouzi; T. Choong (E-Journal of Chemistry)
This work investigated the reduction of chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solids (TSS) and the concentration of heavy metals of wastewater from a steel making plant. Adsorption experiments were carried out by electric arc furnace slag (EAFS) in a fixed-bed column mode. The raw wastewater did not meet the standard B limitations, having high values of BOD, COD, TSS, Iron, Zinc, Manganese and Copper. After passing through the fixed bed column, BOD, COD and TSS values decreased to 1.6, 6.3 and <2 mgL-1, respectively while the concentration of Iron, Zinc, Manganese and Copper were 0.08, 0.01, 0.03 and 0.07 mgL-1, respectively. The results confirmed that EAFS can be used as an efficient adsorbent for producing treated water that comply with the Standard B limitations for an industrial effluent.